MNEs, FDI, inequality and growth. Issue 3 (6th December 2018) - P. Doh, Jonathan
Abstract : Purpose: The relationship among foreign direct investment, multinationals, inequality and growth is a vexing one that has occupied considerable scholarly and practical attention for many decades. To date, international business scholars have not fully concerned themselves with this issue (Buckley, Doh and Benischke, 2017, for an exception). This paper aims to briefly review this literature and report some of the insights of this work. The author draws from and integrates this literature, concluding that multinationals and the foreign investment that emanate from them have a generally positive impact on growth and a generally negative impact on income and wealth equality. The author then details some of the potential contributions MNEs can make to attenuate the negative relationship of foreign direct investment (FDI) on equality, concluding that governments and their policies are the primary vehicle for addressing wealth and income inequality. Design/methodology/approach: This paper is an essay. Findings: The relationship between inequality, growth and FDI is complex. On balance, FDI contributes to growth but may exacerbate inequality under some conditions. More research needs to be conducted, and policymakers need to carefully consider these nuanced relationships. Originality/value: The paper provides review of the relationship of FDI, growth and inequality.